The Edinburgh companion to Atlantic literary studies - Eckel, Leslie Elizabeth; Elliott, Clare (Clare Frances) (Edinburgh University Press, 2016)
New and original collection of scholarly essays examining the literary complexities of the Atlantic world system. This Companion offers a critical overview of the diverse and dynamic field of Atlantic literary studies, with contributions by distinguished scholars on a series of topics that define the area. The essays focus on literature and culture from first contact to the present, exploring fruitful Atlantic connections across space and time, across national cultures, and embracing literature, culture and society. This research collection proposes that the analysis of literature and culture does not depend solely upon geographical setting to uncover textual meaning. Instead, it offers Atlantic connections based around migration, race, gender and sexuality, ecologies, and other significant ideological crossovers in the Atlantic World. The result is an exciting new critical map written by leading international researchers of a lively and expanding field. Key Features. Offers an introduction to the growing field of Atlantic literary studies by showcasing current work engaged in debate around historical, cultural and literary issues in the Atlantic World Includes 26 newly-commissioned scholarly essays by leading experts in Atlantic literary studies Fuses breadth of historical knowledge with depth of literary scholarship Considers the full range of intercultural encounters around and across the Atlantic Ocean This Companion offers a critical overview of the diverse and dynamic field of Atlantic literary studies, with contributions by distinguished scholars on a series of topics that define the area. The essays focus on literature and culture from first contact to the present, exploring fruitful Atlantic connections across space and time, across national cultures, and embracing literature, culture and society. This research collection proposes that the analysis of literature and culture does not depend solely upon geographical setting to uncover textual meaning. Instead, it offers Atlantic connections based around migration, race, gender and sexuality, ecologies, and other significant ideological crossovers in the Atlantic World. The result is an exciting new critical map written by leading international researchers of a lively and expanding field.